Heterocyclic organosilicon compounds separation by preparative gas chromatography - G. N. Turkeltaub; N. G. Komalenkova; E. A. Chernyshev (Тонкие химические технологии, 2008)
The preparative gas chromatography method has been used for isolation of heterocyclic organosilicon compounds boiling up to 400o C. The ways are shown for solution of problems which arise in the course of isolation of such high boiling substances.